AN EXAMINATION OF PARENTAL SATISFACTION WITH CHILDCARE SERVICES IN HOSPITAL-AFFILIATED PRESCHOOLS IN TAIWAN - Wei, Ching-Kuo; Liao, Mao-Hung; Chin, Ting-Chih (PEOPLE: International Journal of Social Sciences, 2024)
This study analyzed parents’ satisfaction towards the facilities, child care service, and environment of hospital- affiliated Preschools in Taiwan. Suggestions were provided for hospital-affiliated Preschools to improve the service satisfaction. The research questionnaires for this study were distributed from September to November 2023, as the questionnaire survey method was adopted to study the service satisfaction of eight hospital-affiliated Preschools in Taiwan. A total of 1183 questionnaires were sent out, and 736 valid questionnaires were retrieved. The questionnaire was reviewed and revised by three experts. The overall Cronbach’s Alpha was 0.968, and the data were statistically analyzed by SPSS.The results of the study revealed the following. There were no significant differences in all dimensions in terms of the demographic variables of age and occupation, while there were significant differences in the educational level for all dimensions.In terms of hospital location, it was found that the hospitals in the northern part of Taiwan were better than those in the southern part of Taiwan. The correlations between all the dimensions were found to be highly significant and positive in the analysis. The education and care dimension had the highest impact on the child care services. Parents attached the highest importance to the education and care dimension of child care services, so Preschools should do their best in terms of teacher qualifications, teaching methods, teaching materials and teaching aids in order to gain parents’ trust. In addition, all dimensions were interlocked, so as long as one of the dimensions can be effectively improved, the other dimensions would also improve. It is suggested that all dimensions should be paid attention to and developed, so that not only the parents can see them, but also the children can grow up safely and happily, and service satisfaction could be greatly improved.